Myocardial glycophagy — A specific glycogen handling response to metabolic stress is accentuated in the female heart - Reichelt, M.E.; Mellor, K.M.; Curl, C.L.; Stapleton, D.; Delbridge, L.M.D. (Journal of molecular and cellular cardiology, 2013)
Cardiac metabolic stress is a hallmark of many cardiac pathologies, including diabetes. Cardiac glycogen mis-handling is a frequent manifestation of various cardiopathologies. Diabetic females have a higher risk of heart disease than males, yet sex disparities in cardiac metabolic stress settings are not well understood. Oestrogen acts on key glycogen regulatory proteins. The goal of this study was to evaluate sex-specific metabolic stress-triggered cardiac glycogen handling responses. Male and female adult C57Bl/6J mice were fasted for 48h. Cardiac glycogen content, particle size, regulatory enzymes, signalling intermediates and autophagic processes were evaluated. Female hearts exhibited 51% lower basal glycogen content than males associated with lower AMP-activated-kinase (AMPK) activity (35% decrease in pAMPK:AMPK). With fasting, glycogen accumulated in female hearts linked with decreased particle size and upregulation of Akt and AMPK signalling, activation of glycogen synthase and inactivation of glycogen phosphorylase. Fasting did not alter glycogen content or regulatory proteins in male hearts. Expression of glycogen autophagy marker, starch-binding-protein-domain-1 (STBD1), was 63% lower in female hearts than males and increased by 69% with fasting in females only. Macro-autophagy markers, p62 and LC3BII:I ratio, increased with fasting in male and female hearts. This study identifies glycogen autophagy (‘glycophagy’) as a potentially important component of the response to cardiac metabolic stress. Glycogen autophagy occurs in association with a marked and selective accumulation of glycogen in the female myocardium. Our findings suggest that sex-specific differences in glycogen handling may have cardiopathologic consequences in various settings, including diabetic cardiomyopathy. •Female basal cardiac glycogen stores are markedly lower than male.•Females exhibit cardiac glycogen accumulation in response to metabolic stress.•Fasting activates myocardial Akt and AMPK signalling in females selectively.•Myocardial glycophagy signalling is evident, with potential for oestrogen regulation.•Glycogen dysregulation may underlie increased risk in female diabetic hearts.